2005
DOI: 10.1177/0363546504271208
|View full text |Cite
|
Sign up to set email alerts
|

The Posterolateral Corner of the Knee

Abstract: Results with repair followed by early motion rehabilitation have been significantly inferior when compared with results from reconstruction using the modified 2-tailed technique. The authors now use reconstruction rather than repair in the majority of patients who sustain posterolateral corner tears after high-energy injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
282
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(295 citation statements)
references
References 23 publications
6
282
0
7
Order By: Relevance
“…Numerous techniques have been attempted, such as lateral advancement, tenodesis of the biceps, and repair or reconstruction of the structures. [1][2][3][4] According to Stannard et al, 3 better results have been obtained with reconstruction techniques. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous techniques have been attempted, such as lateral advancement, tenodesis of the biceps, and repair or reconstruction of the structures. [1][2][3][4] According to Stannard et al, 3 better results have been obtained with reconstruction techniques. …”
Section: Discussionmentioning
confidence: 99%
“…The current tendency is to reconstruct both the ACL and the structures of the PLC, rather than repairing the latter. [1][2][3][4] In injuries involving multiple segments, a potential problem with reconstruction is the convergence of femoral tunnels in the lateral walls in the case of ACL and PLC reconstruction and in the medial walls in the case of posterior cruciate ligament and medial collateral ligament reconstruction. 5,6 As a solution to this problem, we propose a combined technique for reconstruction of the ACL and PLC with a single tunnel in the lateral femoral wall.…”
mentioning
confidence: 99%
“…12 Higher failure rates have been shown with lateral-sided repairs versus reconstruction in the multiligament-injured knee. 13,14 Fig 6. The 9 Â 25emm femoral socket is reamed and tapped, and the calcaneal bone plug is fixed in place with a 7 Â 25emm BioComposite interference screw.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for advocating early surgery in multiligament knee injuries is that the collaterals can be repaired; the repair becomes increasingly difficult two to three weeks after surgery. However, recent literature suggests that reconstruction of the PLC is better than repair, 28,29 and therefore, if one is contemplating a reconstruction, an early surgery is not a necessity. Giannoudis et al 30 reported five cases of knee dislocation with ipsilateral femoral shaft fractures.…”
Section: Management Of the Knee Dislocationmentioning
confidence: 99%